2005
DOI: 10.1081/jdi-200065240
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Attenuates Changes in Nitric Oxide Levels, Renal Oxidative Stress, and Nephrotoxicity Induced by Cyclosporine

Abstract: Cyclosporine A (CsA) is a potent and effective immunosuppressive agent, but its action is frequently accompanied by severe renal toxicity. The causes for the nephrotoxicity of CsA have not been fully elucidated. Intrarenal vasoconstriction induced by several different mediators, both in humans and experimental animals, have been proposed. To determine if the renal alterations are mediated directly by cyclosporine or by secondary hemodynamic alterations induced by cyclosporine, we evaluated if nifedipine preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The beneficial effect of EPL on CsA-induced tissue injury could be accomplished through a direct effect on tubular epithelial target cells or indirectly by the antihypertensive effect. Clinical and experimental animal studies, however, have demonstrated that normalization of BP per se does not prevent deterioration of renal function during CsA-treatment [4,8,19,20]. In accord with a direct effect, calcineurin is co-localized with MR in the distal aldosterone-sensitive segment of the nephron [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effect of EPL on CsA-induced tissue injury could be accomplished through a direct effect on tubular epithelial target cells or indirectly by the antihypertensive effect. Clinical and experimental animal studies, however, have demonstrated that normalization of BP per se does not prevent deterioration of renal function during CsA-treatment [4,8,19,20]. In accord with a direct effect, calcineurin is co-localized with MR in the distal aldosterone-sensitive segment of the nephron [21].…”
Section: Discussionmentioning
confidence: 99%
“…by angiotensin converting enzyme inhibitors [4], calcium channel antagonists [19], or angiotensin II receptor blockade [20], these treatments do not improve the long-term clinical outcome. Angiotensin II has been suggested to be responsible for up-regulation of fibrogenic pathways [24], but the observation that MR blockade protects against tissue injury suggests that aldosterone is also involved [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nifedipine, the most effective calcium blocker, was more than two-fold potent compared to propranolol, achieving significant effect at 10 μ M. Nifedipine protective role on LP using reduced glutathione as model marker was recently described (Ray et al [ 190 ]). Antiperoxidative properties of CA nifedipine and its analogues were explored in different systems/pathogenic processes: atherogenesis (Henry [ 165 ]), brain focal ischemia (Yamato et al [ 191 ]), nephroprotection related to cyclosporine intake (Chander and Chopra [ 192 ]), and hepatoprotection related to intake of diethyldithiocarbamate (Gaafa et al [ 193 ]). Recent data suggest that nifedipine action as protector for endothelial cells proceeds independently from its CA properties.…”
Section: 14-dihydropyridines: a Separate Group Of Bioantioxidantsmentioning
confidence: 99%
“…The former have a direct action on the vasculature to exert a hypotensive effect, whereas the latter are considered to be sympathoinhibitory. Moreover, there are reports suggesting that L‐type Ca 2+ channel blockers have renal protective activity, as seen in renal injury models 8–11 characterized by exaggerated sympathetic tone 12,13 . In this context, considering the renoprotective effects of L‐type Ca 2+ channel blockers along with their well‐known hypotensive effect, we have hypothesized that they may also have an unexplored inhibitory activity on enhanced vascular responsiveness to catecholamines in pathological states characterized by renal impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin is known for its severe nephrotoxicity leading to renal failure 14,15 . It has been observed that cisplatin‐induced renal failure is accompanied by reduced renal blood flow (RBF) associated with increased renal vascular resistance, which may be caused by the enhanced responsiveness of the renal vasculature to renal sympathetic nerve activity and circulating catecholamines 9,10 . In recent studies, we have shown that in cisplatin‐induced renal failure rats vascular tone was likely enhanced, as reflected by increased responsiveness of the renal vasculature to neurally and adrenergically induced vasoconstriction 16,17 …”
Section: Introductionmentioning
confidence: 99%